Analisis Pengaruh Pendapatan Asli Daerah, Angkatan Kerja, dan Sektor Parawisata Terhadap Pertumbuhan PDRB di Kabupaten Toba Samosir - Romian Simbolon, Sophia Amanda (Universitas Labuhanbatu, 2023)
The economic growth of a region is reflected in the Gross Regional Domestic Product (GRDP). Toba Samosir Regency, one of the regencies in North Sumatra Province, is an area that has considerable tourism potential. This study aims to analyze the effect of Regional Original Income (PAD), Work Force (AK), and the tourism sector on GRDP growth in Toba Samosir Regency. The data used in this study is secondary data for 2010-2019 from the BPS of Toba Samosir Regency. The analytical method used is multiple linear regression with the Ordinary Least Square (OLS) technique. The results of the analysis show that PAD, AK, and the tourism sector have a positive and significant effect on GRDP growth in Toba Samosir Regency. The results of the coefficient of determination (R-squared) show that PAD, AK, and the tourism sector are able to explain the variation in GRDP growth of 87.6%. The results of the t test show that the variables PAD, AK, and the tourism sector have a significant influence on GRDP growth. Of the three variables, the tourism sector has the greatest influence on GRDP growth in Toba Samosir Regency. In conclusion, increasing PAD, increasing the number of AK, and developing the tourism sector can increase GRDP growth in Toba Samosir Regency. The Toba Samosir Regency Government is expected to pay attention to and develop the tourism sector as a sector with great potential in increasing regional economic growth.